A cotton-like comfortable stretch aromatic fabric of two-component material and a preparation method thereof
By blending cotton and polyester fibers into a two-component material and combining it with specific treatments of spandex and functional fibers, a cotton-feeling, comfortable, elastic, and aromatic fabric with excellent breathability, moisture absorption, and antibacterial properties is prepared. This solves the problem of insufficient elasticity and breathability of cotton fabrics in sportswear, and improves the overall performance and comfort of sportswear.
Patent Information
- Application Number
- CN202511160251.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-08-19
AI Technical Summary
Existing cotton fabrics used in sportswear suffer from poor elasticity, insufficient breathability, and inadequate skin-friendliness, making it difficult to meet the demands of high-intensity sports activities.
Using two-component materials, including cotton fiber, polyester fiber, spandex fiber and functional fiber, and through specific textile processes and fragrance treatment, a cotton-feeling comfortable elastic fragrance fabric with breathability, moisture absorption, elasticity and antibacterial properties is prepared.
It significantly enhances the breathability and moisture absorption of the fabric, improves its softness and comfort, and has good antibacterial properties, thereby increasing resource utilization and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fabric weaving, in particular to a cotton-feeling comfortable elastic aromatic fabric of bicomponent material and a preparation method thereof. BACKGROUND
[0002] Consumers' demand for sportswear has shifted from basic functionality to a combination of "technology + comfort + fashion", with particular emphasis on the breathability, elasticity, skin-friendliness and environmental friendliness of the fabric.
[0003] In the prior art, when traditional cotton fabric uses pure cotton fabric, it has good moisture absorption but poor elasticity and is prone to deformation, making it difficult to meet the needs of high-intensity sports. When synthetic fibers are used, the elasticity is excellent but the breathability and skin-friendliness are insufficient. Based on this, the present application provides a cotton-feeling comfortable elastic aromatic fabric of bicomponent material and a preparation method thereof. SUMMARY
[0004] The present application aims to provide a cotton-feeling comfortable elastic aromatic fabric of bicomponent material and a preparation method thereof. The cotton-feeling comfortable elastic aromatic fabric prepared by the present application not only has good breathability, moisture absorption and elasticity, but also has excellent antibacterial performance, effectively improving the performance of the cotton-feeling comfortable elastic aromatic fabric.
[0005] To achieve the above-mentioned purpose, the present application provides the following technical solution: a cotton-feeling comfortable elastic aromatic fabric of bicomponent material, comprising the following raw materials by weight: cotton fiber 50-70 parts, polyester fiber 30-50 parts, spandex fiber 8-15 parts, functional fiber 3-8 parts and aromatic agent 1-3 parts.
[0006] Further, the cotton fiber uses long-wool cotton fiber or fine-wool cotton fiber, and the polyester fiber uses shaped polyester with a cross-shaped cross section.
[0007] Further, the spandex fiber is a mixed fiber of melt-spun spandex and dry-spun spandex, with a mass ratio of melt-spun spandex to dry-spun spandex being (3-5):1, and is pre-drafted to an original length of 3 times by a drafting machine.
[0008] Further, the functional fiber includes sunflower stem nanofiber and spent grain short fiber, which are mixed by an air-laid machine with a uniformity CV of less than or equal to 8%, and the mass ratio of sunflower stem nanofiber to spent grain short fiber is (2-4):1.
[0009] Further, the sunflower stem nanofiber is prepared by the following method: selecting agricultural waste sunflower stem, cleaning, crushing and drying, then soaking in a stainless steel basin containing a mixed solution, placing the stainless steel basin in a water bath, setting the temperature to 85-90℃, soaking for 3-4h, taking out and adding to a double-thread rod extruder, continuously extruding at 160-180℃ for 20-40min, screw rotation speed 70-90r / min, extrusion pressure 10-14Mpa, obtaining crude fiber, placing the crude fiber in a ball mill, using zirconium oxide balls as medium, mass ratio of crude fiber to zirconium oxide balls 5:1, and grinding under nitrogen protection for 4-6h, obtaining sunflower stem nanofiber.
[0010] Further, the mixed solution is prepared by mixing sodium sulfate, potassium hydroxide and deionized water, mass ratio of sodium sulfate, potassium hydroxide and deionized water 1.5:4:100, mass ratio of mixed solution to sunflower stem (12-18):1, rotation speed of ball mill 200-300r / min, and water content of crude fiber after extrusion less than or equal to 8%.
[0011] Further, the spent grain short fiber is prepared by the following method: selecting waste spent grain, washing with water, then soaking in a reaction solution containing 2-4% cellulase and 0.5-1% xylanase, placing in a water bath, setting the temperature to 45-50℃, and enzymatic reaction for 12-18h, mass ratio of spent grain to reaction solution (12-18):1, obtaining spent grain cellulose, placing the spent grain cellulose in a reaction kettle containing butylmethyl imidazole chloride ionic liquid, adding 3-5% nanosilica of the mass of spent grain cellulose, mass ratio of spent grain cellulose to butylmethyl imidazole chloride ionic liquid 1:(13-19), setting the stirring speed to 300-500r / min, temperature to 50-80℃, and continuously stirring for 3-6h, filtering to obtain spinning dope, passing the spinning dope through a spinning device with a 0.1-0.15mm spinneret, setting the spinning speed to 40-60m / min, at the same time placing the spinning stream in a coagulation tank containing a coagulation solution composed of 10-15% ethanol and 2-4% citric acid, residence time 50-70s, setting the temperature of the coagulation solution to 20-26℃, completing the coagulation of spent grain fiber, and performing two-stage heat drawing treatment on the spent grain fiber through a heat drawing device, first-stage draw ratio controlled at 25-35%, bath temperature 60℃, second-stage draw ratio 15-20%, bath temperature raised to 90℃, completing the preparation of spent grain short fiber.
[0012] Further, the fragrance is prepared by the following method: β-cyclodextrin and deionized water are added to a stainless steel stirring reaction kettle, the temperature is set to 40-60°C, and stirring is carried out at 300-500 r / min for 5-10 min, then lavender essential oil and peppermint essential oil are added to a clean stainless steel basin, and a stirrer is stirred at 300-500 r / min for 5-10 min, and then taken out and added dropwise to the stainless steel stirring reaction kettle, and stirring is continued at 600-800 r / min for 1-3 h to obtain a fragrance liquid, the mass ratio of the lavender essential oil and the peppermint essential oil is 3:1, and deionized water is taken separately, heated to 50-80°C by a water bath, and then sodium alginate is added to the deionized water, and stirring is continued at 200-300 r / min for 1-2 h to obtain a strengthening agent, and after the fragrance liquid in the stainless steel stirring reaction kettle is cooled to room temperature, the strengthening agent is added to the stainless steel stirring reaction kettle, and stirring is continued at 200-500 r / min for 30-40 min to complete the preparation of the fragrance.
[0013] Further, the mass ratio of the β-cyclodextrin and the deionized water is 8:100, the total mass of the lavender essential oil and the peppermint essential oil is 2-2.5 times the mass of the β-cyclodextrin, the mass ratio of the sodium alginate and the deionized water is 3:100, and the mass ratio of the fragrance liquid and the strengthening agent is 1:(1-1.5).
[0014] Further, the preparation method of the cotton comfortable stretch fragrance fabric of the two-component material comprises the following steps:
[0015] Step 1, the appropriate amount of cotton fiber and polyester fiber is selected as needed, and after opening and removing impurities by an opener, mixing is carried out by a multi-warehouse cotton mixer to obtain mixed spinning, and the mixed spinning and functional fibers are premixed by an air-laid machine to control the mixing uniformity CV≤8% to obtain functional spinning;
[0016] Step 2, the preparation of the composite core-spun yarn is completed by taking the spandex fiber as the core yarn and the functional spinning as the sheath layer through a core-spun yarn machine, setting the spindle speed to 12000 r / min, the yarn guide hook angle to 50°, and the yarn tension to 12 cN;
[0017] Step 3, the fabric is knitted by a single-jersey circular knitting machine;
[0018] Step 4, the fabric is placed in an ultrasonic padding combined machine, and a fragrance is used as the bath agent, the mass ratio of the fabric and the fragrance is 1:10, and the fabric is treated for 25 min at an ultrasonic frequency of 40 kHz to complete the fragrance treatment;
[0019] Step 5, the finished aromatic treatment fabric is placed in a microwave hot air combined setting machine, the temperature is set to 110-120 DEG C, the vehicle speed is 15-20 m / min, the overfeed rate is 5-8%, the microwave system power is 8-10 kW, the hot air system power is 55-70 kW, the fabric setting and preparation are completed.
[0020] Compared with the prior art, the beneficial effects of the present application are:
[0021] 1、In the present application, cotton fibers and polyester fibers are mixed and spun, so that the fabric has the comfort and skin-friendly nature of cotton fibers, and the durability and easy care of polyester fibers, spandex fibers are a mixture of melt-spun spandex and dry-spun spandex and are pre-drafted, giving the fabric good elasticity, sunflower stem nanofibers have extremely fine fiber structure and have extremely large specific surface area, and the spent grain short fibers have suitable fiber morphology and performance, when the two are mixed, they are ingeniously embedded in the overall structure of the fabric, further optimizing the arrangement of the fibers, increasing more tiny gaps, opening up more channels for air circulation and water vapor emission, significantly enhancing the air permeability and moisture absorption of the fabric, and interweaving with other fibers, synergistic effect, making the overall structure of the fabric more stable and tough, greatly improving the softness and comfort of the fabric, providing a full range of comfortable experience for the wearer.
[0022] 2、In the present application, the sunflower stem nanofiber in the functional fiber, the phenolic and flavonoid substances with antibacterial activity existing in the preparation process, will be released from the cell tissue under the action of alkaline environment and temperature, so that the fiber has certain antibacterial ability, at the same time, the cellulase and xylanase components in the reaction solution during the preparation of the spent grain short fiber will leave some oligosaccharide or oligosaccharide fragments on the surface or inside of the fiber, and become more rough, forming some small concave-convex structures, which can increase the contact area of the fiber and bacteria, so that the bacteria are more easily adsorbed on the surface of the fiber, at the same time, nano-silicon dioxide has large specific surface area and surface energy, can adsorb bacteria and interact with bacterial cell membrane, destroy the integrity of bacterial cell membrane, make the intracellular substances leak, so as to cause the death of bacteria, so that the finished fabric has high antibacterial function.
[0023] 3、In the present application, the sunflower stem nanofiber is made of waste sunflower stem, and the spent grain short fiber is derived from waste spent grain, which turns waste into treasure, improves resource utilization rate, reduces the pressure of waste on the environment, opens up a new way for the treatment of agricultural waste, and reduces the production cost of the fabric. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the protection scope of the present application.
[0025] It should be noted that the raw materials used in the following embodiments are all commercially available raw materials.
[0026] Embodiment one: a cotton-feeling comfortable elastic aromatic fabric of a two-component material, comprising the following raw materials in parts by weight: 50 parts of cotton fiber, 30 parts of polyester fiber, 8 parts of spandex fiber, 3 parts of functional fiber and 1 part of aromatic agent.
[0027] The cotton fiber is long-wool cotton fiber or fine-wool cotton fiber, and the polyester fiber is shaped polyester with a cross-section.
[0028] The spandex fiber is a mixed fiber of melt-spun spandex and dry-spun spandex, and the mass ratio of the melt-spun spandex to the dry-spun spandex is 3:1, and the mixed fiber is pre-drafted to an original length of 3 times by a drafting machine.
[0029] The functional fiber comprises sunflower stem nanofiber and spent grain short fiber, and the sunflower stem nanofiber and the spent grain short fiber are mixed by an air-laid machine, the uniformity CV is less than or equal to 8%, and the mass ratio of the sunflower stem nanofiber to the spent grain short fiber is 2:1.
[0030] The sunflower stem nanofiber is obtained by the following method: selecting agricultural waste sunflower stem, cleaning, crushing and drying, then soaking in a stainless steel basin containing a mixed solution, placing the stainless steel basin in a water bath, setting the temperature to 85℃, soaking for 3h, taking out and adding into a double-thread rod extruder, continuously extruding at 160℃ for 20min, screw speed 70r / min, extrusion pressure 10Mpa, obtaining crude fiber, placing the crude fiber in a ball mill, using zirconia balls as medium, mass ratio of crude fiber to zirconia balls 5:1, and grinding for 4h under nitrogen protection to obtain sunflower stem nanofiber.
[0031] The mixed solution is obtained by mixing sodium sulfate, potassium hydroxide and deionized water, and the mass ratio of sodium sulfate, potassium hydroxide and deionized water is 1.5:4:100, the mass ratio of the mixed solution to the sunflower stem is 12:1, the rotating speed of the ball mill is 200r / min, and the water content of the extruded crude fiber is less than or equal to 8%.
[0032] The spent grain short fiber is prepared by the following method: selecting waste spent grain, washing with water, soaking in a reaction solution containing 2% cellulase and 0.5% xylanase, placing in a water bath, setting the temperature to 45°C, and enzymatic hydrolysis for 12 hours, the mass ratio of spent grain to reaction solution is 12:1, obtaining spent grain cellulose, placing the spent grain cellulose in a reaction kettle containing butylmethyl imidazole chloride ionic liquid, adding 3% nanosilica based on the mass of the spent grain cellulose, the mass ratio of spent grain cellulose to butylmethyl imidazole chloride ionic liquid is 1:13, setting the stirring speed to 300 r / min, the temperature to 50°C, and continuously stirring for 3 hours, filtering to obtain a spinning dope, passing the spinning dope through a spinning equipment with a 0.1 mm spinneret, setting the spinning speed to 40 m / min, and at the same time, the spinning stream is placed in a coagulation tank containing a coagulation solution composed of 10% ethanol and 2% citric acid, the residence time is 50 s, the temperature of the coagulation solution is set to 20°C, the coagulation of the spent grain fiber is completed, and the spent grain fiber is subjected to two-stage heat drawing treatment through a heat drawing equipment, the first-stage draw ratio is controlled at 25%, the bath temperature is 60°C during drawing, the second-stage draw ratio is 15%, and the bath temperature is raised to 90°C, the preparation of the spent grain short fiber is completed.
[0033] The fragrance is prepared by the following method: adding β-cyclodextrin and deionized water to a stainless steel stirring reaction kettle, setting the temperature to 40°C, and stirring at 300 r / min for 5 min, then adding lavender essential oil and peppermint essential oil to a clean stainless steel basin, and stirring with a stirrer at 300 r / min for 5 min, then taking out and adding dropwise to the stainless steel stirring reaction kettle, and continuously stirring at 600 r / min for 1 h to obtain a fragrance liquid, the mass ratio of lavender essential oil to peppermint essential oil is 3:1, and deionized water is taken separately, heated to 50°C by a water bath, then sodium alginate is added to the deionized water, and continuously stirred at 200 r / min for 1 h to obtain a reinforcing agent, after the fragrance liquid in the stainless steel stirring reaction kettle is cooled to room temperature, the reinforcing agent is added to the stainless steel stirring reaction kettle, and continuously stirred at 200 r / min for 30 min to complete the preparation of the fragrance.
[0034] The mass ratio of β-cyclodextrin to deionized water is 8:100, the total mass of lavender essential oil and peppermint essential oil is 2 times the mass of β-cyclodextrin, the mass ratio of sodium alginate to deionized water is 3:100, and the mass ratio of fragrance liquid to reinforcing agent is 1:1.
[0035] The preparation method of the cotton-feeling comfortable elastic fragrance fabric of the two-component material comprises the following steps:
[0036] Step 1: the appropriate amount of cotton fiber and polyester fiber is selected as needed, opened and cleaned by an opener, mixed by a multi-warehouse cotton mixer to obtain mixed spinning, and the mixed spinning and functional fibers are pre-mixed by an air-laid machine to control the mixing uniformity CV≤8% to obtain functional spinning.
[0037] Step 2, the preparation of the composite core-spun yarn is completed by a core-spun machine with spandex fiber as the core yarn and functional yarn as the sheath, the spindle speed is set to 12000 r / min, the guide hook angle is 50°, and the yarn tension is 12 cN;
[0038] Step 3, the fabric is knitted by a single-jersey circular knitting machine;
[0039] Step 4, the fabric is placed in an ultrasonic padding machine, and a fragrance is used as the bath agent, the mass ratio of the fabric to the fragrance is 1:10, the ultrasonic frequency is 40 kHz, and the treatment time is 25 min, so as to complete the fragrance treatment;
[0040] Step 5, the fabric after the fragrance treatment is placed in a microwave-hot air combined setting machine, the temperature is set to 110℃, the speed is 15 m / min, the overfeed rate is 6.5%, the microwave system power is 9 kW, and the hot air system power is 55 kW, so as to complete the setting and preparation of the fabric.
[0041] Example Two: A cotton-feeling comfortable and elastic fragrance fabric of a bicomponent material, comprising the following raw materials in parts by weight: cotton fiber 60 parts, polyester fiber 40 parts, spandex fiber 11 parts, functional fiber 5.5 parts, and fragrance 2 parts.
[0042] The cotton fiber is long-fleece cotton fiber or fine-fleece cotton fiber, and the polyester fiber is shaped polyester with a cross-section.
[0043] The spandex fiber is a mixed fiber of melt-spun spandex and dry-spun spandex, the mass ratio of the melt-spun spandex to the dry-spun spandex is 4:1, and the pre-drafting is performed by a drafting machine to 3 times the original length.
[0044] The functional fiber includes sunflower stem nanofiber and spent grain short fiber, which are mixed by an air-laid machine, the uniformity CV is ≤8%, and the mass ratio of the sunflower stem nanofiber to the spent grain short fiber is 3:1.
[0045] The sunflower stem nanofiber is prepared by the following method: agricultural waste sunflower stems are selected, cleaned, crushed, and dried, then soaked in a stainless steel basin containing a mixed solution, the stainless steel basin is placed in a water bath kettle, the temperature is set to 87.5℃, and the soaking time is 3.5 h, then taken out and added into a double-thread extruder, continuously extruded at 170℃ for 30 min, the screw speed is 80 r / min, the extrusion pressure is 12 Mpa, the crude fiber is obtained, the crude fiber is placed in a ball mill with zirconia balls as the medium, the mass ratio of the crude fiber to the zirconia balls is 5:1, and the grinding is performed under nitrogen protection for 5 h to obtain the sunflower stem nanofiber.
[0046] The mixed solution is prepared by mixing sodium sulfate, potassium hydroxide and deionized water, the mass ratio of sodium sulfate, potassium hydroxide and deionized water is 1.5:4:100, the mass ratio of the mixed solution to the sunflower stem is 15:1, the rotating speed of the ball mill is 250r / min, and the water content of the coarse fiber after extrusion is less than or equal to 8%.
[0047] The spent grain short fiber is prepared by the following method: selecting waste spent grain, washing with water, soaking in a reaction solution containing 3% cellulase and 0.75% xylanase, placing in a water bath, setting the temperature to 47.5℃, and enzymatic reaction for 15h, the mass ratio of spent grain to reaction solution is 15:1, obtaining spent grain cellulose, placing the spent grain cellulose in a reaction kettle containing butylmethyl imidazole chloride ionic liquid, adding 4% nanosilica based on the mass of the spent grain cellulose, the mass ratio of spent grain cellulose to butylmethyl imidazole chloride ionic liquid is 1:16, setting the stirring speed to 400r / min and the temperature to 75℃, continuously stirring for 4.5h, filtering to obtain a spinning dope, passing the spinning dope through a spinning device with a 0.125mm spinneret, setting the spinning speed to 50m / min, at the same time, the spinning stream is placed in a coagulation tank containing a coagulation solution composed of 12.5% ethanol and 3% citric acid, the residence time is 60s, the temperature of the coagulation solution is set to 23℃, the coagulation of the spent grain fiber is completed, and the spent grain fiber is subjected to two-stage heat drawing treatment through a heat drawing device, the first-stage draw ratio is controlled at 30%, the bath temperature is 60℃ during drawing, the second-stage draw ratio is 17%, and the bath temperature is raised to 90℃, the preparation of the spent grain short fiber is completed.
[0048] The fragrance is prepared by the following method: adding β-cyclodextrin and deionized water to a stainless steel stirring reaction kettle, setting the temperature to 50℃, and stirring at 400r / min for 7.5min, then adding lavender essential oil and peppermint essential oil to a clean stainless steel basin, and stirring with a stirrer at 400r / min for 7.5min, then taking out and adding dropwise to the stainless steel stirring reaction kettle, continuously stirring at 700r / min for 2h to obtain a fragrance liquid, the mass ratio of lavender essential oil to peppermint essential oil is 3:1, and deionized water is taken separately, heated to 65℃ by a water bath, then sodium alginate is added to the deionized water, continuously stirred at 250r / min for 1.5h to obtain a strengthening agent, after the fragrance liquid in the stainless steel stirring reaction kettle is cooled to room temperature, the strengthening agent is added to the stainless steel stirring reaction kettle, continuously stirred at 350r / min for 35min, and the preparation of the fragrance is completed.
[0049] The mass ratio of β-cyclodextrin to deionized water is 8:100, the total mass of lavender essential oil and peppermint essential oil is 2.25 times the mass of β-cyclodextrin, the mass ratio of sodium alginate to deionized water is 3:100, and the mass ratio of the fragrance liquid to the strengthening agent is 1:1.25.
[0050] The application relates to a preparation method of a cotton-feeling comfortable elastic aromatic fabric of a two-component material, which comprises the following steps:
[0051] Step 1: a proper amount of cotton fibers and polyester fibers are selected, opened and removed of impurities through an opener, mixed through a multi-warehouse cotton mixer, mixed spinning is obtained, and functional fibers are pre-mixed through an air-laying machine, so that the uniformity CV is controlled to be less than or equal to 8%, and functional spinning is obtained;
[0052] Step 2: a core-spun yarn machine is used to prepare a composite core-spun yarn by taking the spandex fiber as a core yarn and the functional spinning as a sheath layer, the spindle speed is set to 12000r / min, the yarn guide hook angle is 50 DEG, and the yarn tension is 12cN;
[0053] Step 3: a single-jersey circular knitting machine is used to carry out fabric spinning on the composite core-spun yarn;
[0054] Step 4: the fabric is placed in an ultrasonic dip-padding combined machine, and a fragrance agent is used as a bath agent, the mass ratio of the fabric to the fragrance agent is 1:10, ultrasonic frequency is 40kHz, and the fragrance treatment is completed after 25min;
[0055] Step 5: the fabric after the fragrance treatment is placed in a microwave hot air combined setting machine, the temperature is set to 115 DEG C, the vehicle speed is 17.5m / min, the overfeed rate is 6.5%, the microwave system power is 9kW, the hot air system power is 62kW, and the fabric setting and preparation are completed.
[0056] Example three: a cotton-feeling comfortable elastic aromatic fabric of a two-component material, which comprises the following weight parts of raw materials: cotton fibers 70 parts, polyester fibers 50 parts, spandex fibers 15 parts, functional fibers 8 parts and a fragrance agent 3 parts.
[0057] The cotton fibers are long-fleece cotton fibers or fine-fleece cotton fibers, and the polyester fibers are shaped polyester fibers with a cross-section in a cross shape.
[0058] The spandex fibers are mixed fibers of melt-spun spandex and dry-spun spandex, the mass ratio of the melt-spun spandex to the dry-spun spandex is 5:1, and the mixed fibers are pre-drafted to an original length of 3 times through a drafting machine.
[0059] The functional fibers comprise sunflower stem nanofibers and spent grain short fibers, are mixed through an air-laying machine, and the uniformity CV is less than or equal to 8%, and the mass ratio of the sunflower stem nanofibers to the spent grain short fibers is 4:1.
[0060] The sunflower stem nanofiber is prepared by the following method: selecting agricultural waste sunflower stem, cleaning, crushing and drying, then soaking in a stainless steel basin containing a mixed solution, and placing the stainless steel basin in a water bath, setting the temperature to 90°C, soaking for 4h, then taking out and adding to a double-threaded rod extruder, continuously extruding at 180°C for 40min, screw speed 90r / min, extrusion pressure 14Mpa, to obtain crude fiber, placing the crude fiber in a ball mill, using zirconium oxide balls as the medium, the mass ratio of crude fiber to zirconium oxide balls being 5:1, and grinding under nitrogen protection for 6h to obtain sunflower stem nanofiber.
[0061] The mixed solution is prepared by mixing sodium sulfate, potassium hydroxide and deionized water, the mass ratio of sodium sulfate, potassium hydroxide and deionized water being 1.5:4:100, the mass ratio of the mixed solution to sunflower stem being 18:1, and the rotation speed of the ball mill being 200-300r / min, the water content of the crude fiber after extrusion being less than or equal to 8%.
[0062] The spent grain short fiber is prepared by the following method: selecting waste spent grain, washing with water, then soaking in a reaction solution containing 4% cellulase and 1% xylanase, and placing in a water bath, setting the temperature to 50°C, and enzymatic reaction for 12-18h, the mass ratio of spent grain to reaction solution being 18:1, to obtain spent grain cellulose, placing the spent grain cellulose in a reaction kettle containing butylmethylimidazole chloride ionic liquid, and adding 5% nanosilica based on the mass of the spent grain cellulose, the mass ratio of spent grain cellulose to butylmethylimidazole chloride ionic liquid being 1:19, setting the stirring speed to 500r / min and the temperature to 80°C, and continuously stirring for 6h, filtering to obtain a spinning dope, passing the spinning dope through a spinning equipment with a 0.15mm spinneret, setting the spinning speed to 60m / min, and at the same time, placing the spinning stream in a coagulation tank containing a coagulation solution composed of 15% ethanol and 4% citric acid, the residence time being 70s, and setting the temperature of the coagulation solution to 26°C, to complete the coagulation of the spent grain fiber, and then performing two-stage heat drawing treatment on the spent grain fiber by a heat drawing equipment, the first-stage draw ratio being controlled at 35%, and the bath temperature being 60°C, and the second-stage draw ratio being 20%, and the bath temperature being raised to 90°C, to complete the preparation of the spent grain short fiber.
[0063] The fragrance is prepared by the following method: β-cyclodextrin and deionized water are added to a stainless steel stirring reaction kettle, the temperature is set to 60°C, and stirring is carried out at 500 r / min for 10 min, then lavender essential oil and peppermint essential oil are added to a clean stainless steel basin, and a stirrer is stirred at 500 r / min for 5-10 min, and then taken out and added dropwise to the stainless steel stirring reaction kettle, and stirring is continued at 800 r / min for 1-3 h to obtain a fragrance liquid, the mass ratio of lavender essential oil and peppermint essential oil is 3:1, and deionized water is taken separately, heated to 80°C by a water bath, and then sodium alginate is added to the deionized water, and stirring is continued at 300 r / min for 2 h to obtain a reinforcing agent, and then the reinforcing agent is added to the stainless steel stirring reaction kettle, and stirring is continued at 500 r / min for 40 min to complete the preparation of the fragrance.
[0064] The mass ratio of β-cyclodextrin to deionized water is 8:100, the total mass of lavender essential oil and peppermint essential oil is 2.5 times the mass of β-cyclodextrin, the mass ratio of sodium alginate to deionized water is 3:100, and the mass ratio of the fragrance liquid to the reinforcing agent is 1:1.5.
[0065] The preparation method of the two-component material cotton comfortable stretch fragrance fabric comprises the following steps:
[0066] Step 1: The appropriate amount of cotton fiber and polyester fiber is selected as needed, and after opening and removing impurities by an opener, it is mixed by a multi-warehouse cotton mixer to obtain mixed spinning, and the mixed spinning and functional fiber are premixed by an air-laid machine to control the uniformity CV≤8% to obtain functional spinning;
[0067] Step 2: The composite core-spun yarn is prepared by a core-spun yarn machine with spandex fiber as the core and the functional spinning as the sheath, the spindle speed is set to 12000 r / min, the guide hook angle is 50°, and the yarn tension is 12 cN;
[0068] Step 3: The composite core-spun yarn is knitted into a fabric by a single-jersey circular knitting machine;
[0069] Step 4: The fabric is placed in an ultrasonic padding combined machine, and an aromatic agent is used as a bath agent, the mass ratio of the fabric to the aromatic agent is 1:10, and the fabric is treated under ultrasonic frequency of 40 kHz for 25 min to complete the fragrance treatment;
[0070] Step 5: The fabric after the fragrance treatment is placed in a microwave hot air combined setting machine, the temperature is set to 120°C, the speed is 20 m / min, the overfeed rate is 8%, the microwave system power is 10 kW, and the hot air system power is 70 kW to complete the fabric setting and preparation.
[0071] Comparative Example 1, the difference between the comparative example and Example 1 is that the functional fiber is not added with spent grain short fiber during preparation.
[0072] Comparative Example Two, the difference between this comparative example and Example One is that the functional fiber in this comparative example is not added with sun stalk nanofiber during preparation.
[0073] Comparative Example Three, the difference between this comparative example and Example One is that the polyester fiber is not added during the preparation process of this comparative example.
[0074] Comparative Example Four, the difference between this comparative example and Example One is that the sodium alginate is not added during the preparation of the fragrance in this comparative example.
[0075] Performance test: the fabrics prepared by Example One, Example Two, Example Three, Comparative Example One, Comparative Example Two, Comparative Example Three and Comparative Example Four are tested for performance, and the test items and test methods are as follows,
[0076] Among them, the antibacterial property of the fabric is tested by the shaking flask method, a certain amount of fabric sample is put into the culture solution containing a certain amount of bacteria, and after shaking culture at a certain temperature for a certain time, the number of surviving bacteria in the culture solution is measured by plate counting method, and the antibacterial rate is calculated to evaluate the antibacterial performance;
[0077] The air permeability is tested by YG461E type digital fabric air permeability tester, the fabric sample is fixed on the test hole, and the air quantity per unit area of fabric per unit time under a specified pressure difference is measured by the instrument; the moisture absorption is tested by weighing method, the fabric sample is weighed after equilibrium under standard atmospheric conditions, then it is hung in an environment with specified humidity and temperature, and after a certain time, it is weighed again, the percentage of the weight of water absorbed by the fabric to the original weight is calculated to represent the moisture absorption; the elasticity is tested by LLY-061E type electronic single yarn strength tester, the fabric sample of a certain length is stretched at a certain stretching speed, and the elastic recovery rate of the fabric during stretching is measured to evaluate its elastic performance; the washing fragrance retention rate is tested by measuring the concentration of residual fragrance on the fabric after multiple standard washing procedures using professional instruments such as electronic nose, and comparing it with the fragrance concentration before washing, and calculating the washing fragrance retention rate.
[0078] The test data obtained are recorded in Table 1 below:
[0079]
[0080] It can be seen that the antibacterial property, air permeability, elasticity, moisture absorption and fragrance retention rate of the fabrics prepared by Comparative Examples One, Two, Three and Four are lower than those of Examples One, Two and Three.
[0081] Through comparison and analysis of the relevant data in Table 1, it can be known that the fabric treated by the cotton-feeling comfortable elastic aromatic fabric of two-component material and the preparation method thereof has not only good antibacterial property, air permeability and elasticity, but also excellent moisture absorption. Therefore, the cotton-feeling comfortable elastic aromatic fabric of two-component material and the preparation method thereof have wider market prospect and are more suitable for promotion.
[0082] In the description of the present specification, the description referring to the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0083] The preferred embodiments of the application disclosed above are only used to help explain the application. The preferred embodiments do not describe all the details and limit the application to the specific embodiments. Obviously, many modifications and variations can be made according to the content of the present specification. The present specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the application, so that those skilled in the art can well understand and utilize the application. The application is limited only by the claims and their full scope and equivalents.
Claims
1. A two-component material, cotton-feeling, comfortable, stretch, aromatic fabric, characterized in that: The functional fiber comprises sunflower stem nanofiber and spent grain short fiber, and the mass ratio of the sunflower stem nanofiber to the spent grain short fiber is (2-4):
1. The sunflower stem nanofiber is prepared by the following method: selecting agricultural waste sunflower stems, cleaning, crushing and drying, then soaking in a stainless steel basin containing a mixed solution, placing the stainless steel basin in a water bath, setting the temperature to 85-90 DEG C, soaking for 3-4 hours, then adding to a double-thread rod extruder, continuously extruding at 160-180 DEG C for 20-40 minutes, screw rotation speed 70-90 r / min, extrusion pressure 10-14 MPa, obtaining crude fiber, placing the crude fiber in a ball mill with zirconium oxide balls as the medium, the mass ratio of the crude fiber to the zirconium oxide balls being 5:1, and grinding for 4-6 hours under nitrogen protection to obtain sunflower stem nanofiber. The spent grain short fiber is prepared by the following method: selecting waste spent grain, washing, then soaking in a reaction solution containing 2-4% cellulase and 0.5-1% xylanase, placing in a water bath, setting the temperature to 45-50 DEG C, enzymatic reaction for 12-18 hours, the mass ratio of the spent grain to the reaction solution being (12-18):1, obtaining spent grain cellulose, placing the spent grain cellulose in a reaction kettle containing butylmethyl imidazole chloride ionic liquid, adding 3-5% nanosilica based on the mass of the spent grain cellulose, the mass ratio of the spent grain cellulose to the butylmethyl imidazole chloride ionic liquid being 1:(13-19), setting the stirring speed to 300-500 r / min, the temperature to 50-80 DEG C, continuously stirring for 3-6 hours, filtering to obtain a spinning dope, passing the spinning dope through a spinning device with a 0.1-0.15 mm spinneret, setting the spinning speed to 40-60 m / min, at the same time placing the spinning stream in a coagulation tank containing a coagulation solution composed of 10-15% ethanol and 2-4% citric acid, the residence time being 50-70 s, setting the temperature of the coagulation solution to 20-26 DEG C, completing the coagulation of the spent grain fiber, and performing two-stage heat drawing on the spent grain fiber by a heat drawing device, the first-stage draw ratio being controlled to 25-35%, the bath temperature being 60 DEG C, the second-stage draw ratio being 15-20%, the bath temperature being raised to 90 DEG C, completing the preparation of the spent grain short fiber. The cotton fiber adopts long-wool cotton fiber or fine-wool cotton fiber, and the polyester fiber adopts cross-shaped profiled polyester.
2. The two-component material, cotton-feeling, comfortable, elastic, and fragrant fabric of claim 1, wherein, The spandex fiber is a mixed fiber of melt-spun spandex and dry-spun spandex, the mass ratio of the melt-spun spandex to the dry-spun spandex being (3-5):1, and the mixed fiber is pre-drawn to 3 times the original length by a drawing machine.
3. The two-component material, cotton-feeling, comfortable stretch, aromatic fabric of claim 1, wherein, 4. The two-component material, cotton-feeling, comfortable stretch, aromatic fabric of claim 1, wherein, The mixed solution is prepared by mixing sodium sulfate, potassium hydroxide and deionized water, the mass ratio of sodium sulfate, potassium hydroxide and deionized water is 1.5:4:100, the mass ratio of the mixed solution to sunflower stem is (12-18):1, the rotating speed of the ball mill is 200-300r / min, and the water content of the extruded coarse fiber is less than or equal to 8%.
5. The two-component material, cotton-feeling, comfortable stretch, aromatic fabric of claim 1, wherein, The fragrance is prepared by the following method: β-cyclodextrin and deionized water are added to a stainless steel stirring reaction kettle, the temperature is set to 40-60℃, and stirring is carried out at 300-500r / min for 5-10min, then lavender essential oil and peppermint essential oil are added to a clean stainless steel basin, and a stirrer is stirred at 300-500r / min for 5-10min, and then taken out and added dropwise into the stainless steel stirring reaction kettle, and stirring is continued at 600-800r / min for 1-3h to obtain a fragrance liquid, the mass ratio of the lavender essential oil and the peppermint essential oil is 3:1, and deionized water is taken separately, heated to 50-80℃ by a water bath, then sodium alginate is added to the deionized water, and stirring is continued at 200-300r / min for 1-2h to obtain a strengthening agent, after the fragrance liquid in the stainless steel stirring reaction kettle is cooled to room temperature, the strengthening agent is added to the stainless steel stirring reaction kettle, and stirring is continued at 200-500r / min for 30-40min to complete the preparation of the fragrance.
6. The two-component material, cotton-feeling, comfortable stretch, aromatic fabric of claim 5, wherein, The mass ratio of the β-cyclodextrin and the deionized water is 8:100, the total mass of the lavender essential oil and the peppermint essential oil is 2-2.5 times the mass of the β-cyclodextrin, the mass ratio of the sodium alginate and the deionized water is 3:100, and the mass ratio of the fragrance liquid and the strengthening agent is 1:(1-1.5).
7. The method of making a two-component, cotton-feeling, comfortable stretch, aromatic fabric according to any one of claims 1-6, characterized in that, The method comprises the following steps: Step 1: cotton fibers and polyester fibers are selected as needed, and then subjected to opening and impurity removal by an opener, and then mixed by a multi-warehouse cotton mixer to obtain mixed spinning, and the mixed spinning and functional fibers are premixed by an air-laid machine to control the mixing uniformity CV≤8% to obtain functional spinning; Step 2: a composite core-spun yarn is prepared by a core-spun yarn machine, with spandex fibers as core filaments and functional spinning as sheath layers, the spindle speed is set to 12000r / min, the yarn guide hook angle is 50°, and the yarn tension is 12cN; Step 3: the composite core-spun yarn is subjected to fabric spinning by a single-jersey circular knitting machine; Step 4: the fabric is placed in an ultrasonic padding combined machine, and an aromatic agent is used as a bath agent, the mass ratio of the fabric to the aromatic agent is 1:10, and the fabric is treated under ultrasonic frequency of 40kHz for 25min to complete the aromatic treatment; Step 5: the fabric subjected to the aromatic treatment is placed in a microwave hot air combined setting machine, the temperature is set to 110-120℃, the vehicle speed is 15-20m / min, the overfeed rate is 5-8%, the microwave system power is 8-10kW, and the hot air system power is 55-70kW to complete the fabric setting and preparation.
Citation Information
Patent Citations
Spun-laced compound nonwoven material containing line elastomer, preparation method and equipment thereof
CN101230519A
Novel bio-based bi-component polymer super-elastic super-soft cool multifunctional interwoven fabric
CN114059220A